Inflammasome signaling proteins as biomarkers of COVID-19 - Hadad, Roey; Keane, Robert W.; de Rivero Vaccari, Juan Pablo (Frontiers in Immunology, 2023)
Introduction One of the main characteristics of COVID-19 is an exacerbated inflammatory response that results in cardiometabolic complications and dysfunction in the nervous system. Moreover, these complications may extend beyond the period of active SARS-CoV2 infection and even extend over a year. Thus, it is important to better understand the contribution of the inflammatory responses in COVID-19 patients, not just in the acute phase but also after the infection has subsided. Methods We measured the protein levels of inflammasome signaling proteins using Simple Plex microfluidics technology in patients with an active SARS-CoV2 infection and in recovered patients to determine their potential use as biomarkers of COVID-19. We carried out statistical analyses to identify which proteins were increased in COVID-19 patients with active infection and in recovered patients. The receiver operating characteristics (ROC) were calculated for each analyte to determine their potential fit as biomarkers. Results The inflammasome proteins caspase-1, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), interleukin (IL)-1β and IL-18 were elevated in the plasma of patients with active infection and remained elevated after the infection was resolved for approximately 2 months after. Levels of caspase-1 and ASC continued to increase long after patients had recovered from the infection. Furthermore, when measuring biomarkers of inflammation during active infection, analyses with area under the curve (AUC) values above 0.75 indicated that caspase-1, ASC, IL-1β and IL-18 are reliable biomarkers of the inflammatory response during active COVID-19 infection. Moreover, when measuring biomarkers of inflammation after recovery from active infection, caspase-1 and ASC presented AUC values above 0.9. Discussion These findings indicate that inflammasome signaling proteins can be used to reliably monitor the inflammatory innate immune response in COVID-19 patients.